2009
DOI: 10.1002/pssb.200844402
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of finite‐length silicon carbide nanotubes

Abstract: The electronic properties of silicon carbide nanotubes (SiCNT) as a function of length, were investigated by means of density functional theory (DFT). We found that the increasing nanotube length yields a higher localization of the lowest unoccupied and highest occupied molecular orbitals (LUMO and HOMO), thus affecting the behavior of the band gap and chemical reactivity of the SiCNTs. It is also found that structural stability increases for longer and larger nanotubes. (© 2009 WILEY‐VCH Verlag GmbH & Co.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
2
3
0
Order By: Relevance
“…At the liquid nitrogen temperature (77 K), the substrate electric resistance (hexagonal polytype) was *2 orders of magnitude higher as compared with films. The studied epitaxial layers exhibited n-type conductivity, the concentration of carriers and their mobility at 300 K were 2610 18 cm 73 and 40 cm 2 (V s) 71 , respectively, i.e., sufficiently close to the data in Table 1. Analysis of the results also demonstrated that the low resistance of these layers at liquid helium temperatures may be associated with the presence of the insulator ± metal junction.…”
Section: Propertiessupporting
confidence: 84%
See 1 more Smart Citation
“…At the liquid nitrogen temperature (77 K), the substrate electric resistance (hexagonal polytype) was *2 orders of magnitude higher as compared with films. The studied epitaxial layers exhibited n-type conductivity, the concentration of carriers and their mobility at 300 K were 2610 18 cm 73 and 40 cm 2 (V s) 71 , respectively, i.e., sufficiently close to the data in Table 1. Analysis of the results also demonstrated that the low resistance of these layers at liquid helium temperatures may be associated with the presence of the insulator ± metal junction.…”
Section: Propertiessupporting
confidence: 84%
“…Particularly, the presence of small reflexes in the vicinity of the pronounced (111) peak in b-SiC XRD patterns was mentioned, which was associated with stacking defects. At the same time, the Raman spectra demonstrated peculiarities as compared with those observed earlier, 32 for example, the presence of peaks at 972 and 800 cm 71 . Various temperature conditions of crystallization of a particular SiC polytype depend on experimental conditions and many kinetic parameters.…”
Section: Films and Compactssupporting
confidence: 66%
“…Due to hardware limitations, this resulted to be the best choice allowing us to investigate a wide range of SiCNTs. However, even if for small-diameter SiCNTs this resulted in systems with a low number of atoms, by considering the results of our previous investigation [23], such a limitation may not have a significant impact on the bandgap (and consequently electronegativity) values of the nanotube with a diameter larger than 5 Å, while for diameters below 5 Å, it is reasonable to expect a 15% reduction of the calculated values. A complete list of such SiCNTs is summarized in table 1.…”
Section: Methodsmentioning
confidence: 87%
“…which are obtained by setting the vacuum level (E VAC ) at zero and defining EA = E VAC − E LUMO and IP = E VAC − E HOMO . The values of χ are shown in figure 6 where it can be seen that the reactivity of all the nanotubes decreases with diameter, but it is higher than that of bulk zinc blende SiC (1.5 eV) [28] and of that of armchair SiCNTs [23]. This indicates that SiCNTs can have interesting applications as the walls of chiral SiCNTs seem to be more suitable than those of armchair SiCNTs for being decorated with functional groups and for hydrogen storage purposes.…”
Section: Resultsmentioning
confidence: 99%
“…The studies conducted by G. Alfieri et al, have verified that the diameter and tube length of armchair SiCNTs affects molecular orbitals, bandgap, chemical reactivity, and stability. 20 To synthesize specific materials for various uses, it is essential to physically or chemically modify nanostructures by adding more atoms or molecules. For nanotube-assisted drug delivery in pharmaceutical applications, the addition of biological structures to nanotubes is essential.…”
mentioning
confidence: 99%